2002
DOI: 10.1039/b108816e
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the cell death modes and the associated changes in cellular energy supply in response to AlPcS4-PDT

Abstract: Photodynamic therapy (PDT) can result in both types of cell death, apoptosis or necrosis. Several steps in the induction and execution of apoptosis depend on ATP and the intracellular ATP level has been shown to be one determinant in whether apoptosis or necrosis occurs. Therefore, photochemical damage of cellular targets involved in energy supply might play a crucial role in the mode of cell death being executed. The present study is aimed at the characterization of changes in cellular energy supply and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 36 publications
4
62
0
1
Order By: Relevance
“…Finally, a mode of cell death depends not only on a PDT dose (Plaetzer et al 2002) but also on cell type (Wyld et al 2001. Therefore, dosimetry investigations in different cell types may provide evidence to facilitate the choice of the appropriate application for a certain PS.…”
Section: Dosimetry In Pdt Research and Applicationsmentioning
confidence: 99%
“…Finally, a mode of cell death depends not only on a PDT dose (Plaetzer et al 2002) but also on cell type (Wyld et al 2001. Therefore, dosimetry investigations in different cell types may provide evidence to facilitate the choice of the appropriate application for a certain PS.…”
Section: Dosimetry In Pdt Research and Applicationsmentioning
confidence: 99%
“…Plaetzer proposes that the mode of cell death is related directly to the changes in the ATP pool. Assays of procaspace-3 activation and nuclear fragmentation on human epidermoid carcinoma cell line A431 have shown that while impairment of mitochondrial functions and rapid decrease of ATP are symptomatic of necrotic cell death, the preservation of high ATP levels allows the execution of the apoptotic program (Plaetzer et al 2002). The photosensitized damages on lysosomes are generally less lethal than that sustained by mitochondria (Berg and Moan 1994).…”
Section: Mechanisms Of Cell Death As a Function Of Subcellular Localimentioning
confidence: 99%
“…EVects on the bioenergetics, (Atlante et al 1989;Moreno 1981, 1990) primarily on the mitochondrial permeability transition pore (Salet et al 1997) have been investigated in detail (Dummin et al 1997;Morgan and OseroV 2001;Plaetzer et al 2002). PDT may induce permeabilization of both mitochondrial membranes, dissipation of the transmembrane potential, and a release of apoptosis-related proteins (such as cytochrome c, apoptosis inducing factor, second mitochondria derived activator of caspases and certain procaspases) into the intermembrane space (Almeida et al 2004;Oleinick et al 2002).…”
Section: Mechanisms Of Cell Death As a Function Of Subcellular Localimentioning
confidence: 99%
“…In this technique, patients are administered PPIX or its precursor, 5-aminolevulinic acid (ALA), and reactive oxygen species are generated with local laser irradiation to kill malignant cells or epithelial cells of vascular neoplasms. In addition to the tumoricidal effects of reactive oxygen species, photodynamic therapy also induces energy-demanding apoptotic process by maintaining intracellular ATP levels [66].…”
Section: Porphyrinmentioning
confidence: 99%